Pengaruh Kebijakan Dividen, Keputusan Investasi, dan Risiko Pasar terhadap Nilai Perusahaan yang Dimoderasi Return Saham - Atika Somantri Dewi; Nera Marinda Machdar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Economic growth can be an assessment material for the development of a country's progress. In this case, companies have an important role in advancing the country's economy, in line with the large number of companies that make competition in the business world run tight. A good increase in share prices will provide an increase in company value. The aim of conducting this research is to analyze the influence of dividend policy, investment decisions and market risk on company value which is moderated by stock returns. This research uses qualitative or descriptive methods and is presented in the form of a literature study. The results of this research show that dividend policy, investment decisions and market risk influence company value. Apart from that, dividend policy, investment decisions and market risk can be moderated by stock returns in influencing company value.